2004
DOI: 10.1152/jn.00821.2003
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Visual Space at the Time of Pro- and Anti-Saccades

Abstract: The localization of peri-saccadically flashed objects shows two types of errors: first, a uniform shift in saccade direction, and second, a compression of visual space around the saccade target. Whereas the uniform shift occurs when the experiment is performed in complete darkness compression occurs when additional visual references are available. Thus peri-saccadic mislocalization contains motor and visual components. To distinguish between both factors we compared peri-saccadic localization errors during pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 35 publications
8
27
0
Order By: Relevance
“…All these erroneous trials were discarded for the rest of the study. The mean saccadic latency computed over all subjects was significantly shorter for prosaccades than that for antisaccades, in agreement with previous studies (Awater and Lappe 2004;Brown et al 2006;Dafoe et al 2007;Everling and Fischer 1998;Seidlits et al 2003). In addition, we found that prosaccades reached a significantly faster peak velocity than antisaccades.…”
Section: General Observationssupporting
confidence: 92%
“…All these erroneous trials were discarded for the rest of the study. The mean saccadic latency computed over all subjects was significantly shorter for prosaccades than that for antisaccades, in agreement with previous studies (Awater and Lappe 2004;Brown et al 2006;Dafoe et al 2007;Everling and Fischer 1998;Seidlits et al 2003). In addition, we found that prosaccades reached a significantly faster peak velocity than antisaccades.…”
Section: General Observationssupporting
confidence: 92%
“…Note however, that in comparison to the findings of Morrone et al (1997) with real saccades, the localization bias toward the peripheral target is less pronounced for simulated saccades in our study. Since space compression also tended to be weaker in our real saccade task, different stimulus parameters, such as luminance (Awater and Lappe, 2004), contrast level (Michels and Lappe, 2004) and spatial frequency of the flashed stimulus may primarily account for this difference. Further experiments probing mislocalization shortly before real and simulated saccades with a parametric modulation of these factors are required to resolve the difference.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, Awater and Lappe (2004) reported that the same distortions of visual space are produced during anti-saccades as during pro-saccades. They attributed these distortions to the remapping process in parietal cortex, in accord with the present findings.…”
Section: Discussionmentioning
confidence: 94%